Narrative Review: Potential of Flavonoids from Moringa (Moringa oleifera Lam.) Leaves as Immunomodulators: Tinjauan Naratif: Potensi Flavonoid dari Daun Kelor (Moringa oleifera Lamk.) sebagai Imunomodulator - Poluan, Jesica Carine; Zubair, Muhammad Sulaiman; Ramadani, Arba Pramundita; Hayati, Farida (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Moringa leaves (Moringa oleifera Lamk.) are plants from the Moringaceae family that have many properties and are often used empirically as traditional medicine. One of the benefits of M. oleifera leaves is immunomodulator, which functions to modulate the human immune system in both immunostimulants and immunosuppressants. Objectives: To provide information on the potential of flavonoids in M. oleifera leaves as immunomudulators developed as alternative therapies. Methods: Review of articles using original articles from national and international journals with the keywords "immunomodulator," "immunostimulant," "immunosuppressant," "Flavonoids," and "Moringa oleifera leaf or leaves". Results: Based on a search of various literature studies, M. oleifera leaf extract is proven as an immunomodulator with the most compounds found, namely flavonoids such as quercetin and kaempferol. This content can affect the immune response to trigger or inhibit the proliferation and activation of immune cells in the process of increasing or decreasing the immune system in the body. Conclusions: Moringa leaves have activity as immunomodulators that can help maintain the immune system in the body.